Lower Salaries and No Options? On the Optimal Structure of Executive Pay - DITTMANN, INGOLF; MAUG, ERNST (Journal of Finance, 2007)
ABSTRACT We calibrate the standard principal–agent model with constant relative risk aversion and lognormal stock prices to a sample of 598 U.S. CEOs. We show that this model predicts that most CEOs should not hold any stock options. Instead, CEOs should have lower base salaries and receive additional shares in their companies; many would be required to purchase additional stock in their companies. These contracts would reduce average compensation costs by 20% while providing the same incentives and the same utility to CEOs. We conclude that the standard principal–agent model typically used in the literature cannot rationalize observed contracts.